2016
DOI: 10.3390/ijerph14010022
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Determinants of Bronchial Asthma among Saudi School Children in Southwestern Saudi Arabia

Abstract: The aim here was to study the possible environmental and dietary determinants of asthma among school-aged children in Southwestern Saudi Arabia. In a cross-sectional study on a representative sample in Najran in Southwestern Saudi Arabia using an Arabic version of the modified ISAAC Phase III, parent-administered questionnaire data were collected. Skin prick tests (SPTs) were performed. The study included 1700 school children, out of them 468 (27.5%) were diagnosed with, cases of bronchial asthma and 20.8% (35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 35 publications
5
35
2
Order By: Relevance
“…In this current research, there was a positive significant association between egg consumption and nocturnal dry cough, reported by 12.43% of asthmatic children; this is in accord with what was reported in the previous study in Southwestern Saudi Arabia (9). Moreover, a positive association was observed between seafood and nocturnal dry cough, by 6.48% of total asthmatic children, which in contrast to the finding of the previous study in Southwestern Saudi Arabia (9).…”
Section: Discussion:-supporting
confidence: 89%
See 4 more Smart Citations
“…In this current research, there was a positive significant association between egg consumption and nocturnal dry cough, reported by 12.43% of asthmatic children; this is in accord with what was reported in the previous study in Southwestern Saudi Arabia (9). Moreover, a positive association was observed between seafood and nocturnal dry cough, by 6.48% of total asthmatic children, which in contrast to the finding of the previous study in Southwestern Saudi Arabia (9).…”
Section: Discussion:-supporting
confidence: 89%
“…Exposure to air pollution caused by truck traffic or industry will trigger oxidative stress, inflammation of the airway, and consequently exacerbate asthma in children (16). In the current study, there is a positive significant relationship between nocturnal dry cough/dyspnea and car exhaust fumes, reported by 9% of the total sample, these results were found in previous studies in Southwestern Saudi Arabia (9) and Germany (16). The current study found several different irritants, including dust, perfume, and incense, which exacerbated nocturnal dry cough, dyspnea and wheezing in children.…”
Section: Discussion:-supporting
confidence: 85%
See 3 more Smart Citations